(untitled) (Colombia Medica, 2014)
Objective: To study the NAT2 gene polymorphisms 481T, 590A, and 857A in the Chimila, Wiwa, and Wayuu Indigenous groups of the Colombian Caribbean to determine the frequencies of the allelesNAT2*4, NAT2*5, NAT2*6, and NAT2*7 and to determine the types of acetylation present in these populations. Methods: A total of 202 subjects were studied: 47 Chimila, 55 Wiwa, and 100 Wayuu. The polymorphisms were identified using a real-time PCR method for allelic discrimination designed using Taqman of Applied Biosystems. Results: The following alleles were found at the highest frequency in the following groups: the NAT2*4 allele (wild type) in the Wayuu group (55.3%), the NAT2*5 allele in the Wiwa group (34.5%), and the NAT2*7 allele in the Chimila group (24.2%). A higher frequency of the rapid acetylation status was found in the Wayuu group (31.3%) and Chimila group (29.5%) compared with the Wiwa group (12.7%). The intermediate acetylation status distribution was very similar in all three groups, and the frequency of the slow acetylation status was higher in the Wiwa group (32.7%) compared with the Chimila and Wayuu groups (20.5% and 21.2%, respectively). Conclusion: The results demonstrated the allelic distribution and pharmacogenetic differences of the three groups studied and revealed the most frequent acetylation status and phenotype. Because of the high prevalence of slow acetylations, a greater incidence of tuberculosis (TB) drug-induced hepatotoxicity is predicted in these populations, with a higher frequency in the Wiwa group.